PENGARUH KECERDASAN INTELEKTUAL TERHADAP KESULITAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KIMIA - Tin Rosidah; Eny Winaryati; Wiwik Indah Kusumaningrum (Universitas Muhammadiyah Semarang, 2017)
The condition in a learning process characterized the certain barriers to reach study results called by a learning difficulty. A learning disability students wouldhave an impact on student learning achievements. The research is a follow-upto previous studies said that intelligence quotient (IQ) have an significantagainst difficulties study results students in subjects chemical. This studyfocused on the relationship between intelligence quotient and student’sdifficulty in chemistry class at SMA N 9 Semarang. It was a descriptivequalitative research which used observation, interview, documentation, andquestionnaire as the method to collect the data. From the result it can beconcluded that there was relationship between student’s learning difficulty andthe intelligence quotient, especially on student’s reasoning ability during thechemistry class. The ability to think students include computation capabilitiesand memorization.This proved that hypothesis right, namely intelligencequotient have an significant against difficulties study results students inparticular to the matter memorization in matter a periodic system element on the subjects of chemical in SMA N 9 Semarang. Keywords:Intelligence quotient (IQ), Learning difficulty, Chemistry